THE IMPOSSIBILITY TO BE ‘LOST IN TRANSFORMATION’ (The Pretoria Student Law Review, 2021)
The purpose of this work is an attempt to argue that South Africa as a society cannot be lost in transformation, but that the process of transformation can be misguided or ineffective is, in my opinion, irrefutable. Because of our particular history, equality jurisprudence will be used as the subject matter to indicate whether our society can be lost in transformation. In the first instance, I discuss the condictiones sine quo non of post-apartheid South African equality jurisprudence in the second part. Thereafter, in the third part, the aspirational end — the achievement of equality — serves to identify, through our constitutional values and section 9 of the Constitution, three power relations which require addressing for our society to transform. With reference to Legal feminism, Critical Race Theory and Queer Theory, patriarchy, white supremacy and heteronormativity are identified as power relations that are the, current, object of transformation in our society.
Keywords: transformation; post-apartheid South Africa; equality jurisprudence; constitutional values; the Constitution